Peran Kepercayaan Pada Pemerintah Sebagai Variabel Mediasi Antara Faktor Penentu Kepatuhan Dan Kepatuhan Wajib Pajak - Anugrah, Audrey; Zaitul, Zaitul; Herawati, Herawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this study was to investigate the effect of the tax payer awareness, tax payer morale and governmen power on tax compliance.besides, this study also determine the role of trust on government as a mediating variable.. The object of this research is PBB-P2 tax payers in Pasaman Barat Regency with dinal sample of 100 tax payers. This study uses primery databy disributing the questionnaires to taxpayers. Methods of data analysis is applying Structural Equation model (SEM)-PLS using Smart-pls 3.2.8. tax payer awareness has a negative effect on tax compliance. Trust on government mediated the relationship government power and tax compliance (full mediation). This study has a pratical dan theoritical implications and it discuss in this paper.